The Joshua plan - Robertson, Pat.; Robertson, Gordon Perry, 1958-; Christian Broadcasting Network (U.S.) (Virginia Beach, Va. : Christian Broadcasting Network, 2008)
In Pat and Gordon Robertson's latest teaching, you'll discover the power of the Holy Spirit's anointing, how God supernaturally provides for His people, how to avoid wrong choices, how to choose the path to blessing and peace, and how "remembering" can build your faith.--from Publisher's website.
The land of promise. I. Remembering -- II. God's supernatural provision -- III. Living in the new covenant.
Keywords: Christian life; Spiritual life; Bible